Treatment of failed aortic bioprostheses: An evaluation of conventional redo surgery and transfemoral transcatheter aortic valve-in-valve implantation. (1st February 2020) - Woitek, Felix J.; Stachel, Georg; Kiefer, Philipp; Haussig, Stephan; Leontyev, Sergey; Schlotter, Florian; Mende, Meinhard; Hommel, Jennifer; Crusius, Lisa; Spindler, Aileen; Mohr, Friedrich W.; Schuler, Gerhard; et al.
Abstract: Background: The use of bioprostheses for surgical aortic valve replacement increased substantially within the last years. In case of prosthesis failure, re-SAVR is standard of care, whereas valve-in-valve deployment of a transfemoral transcatheter aortic valve prosthesis (VinV-TFAVI) has recently emerged as an alternative. We sought to evaluate early safety, clinical efficacy, and all-cause 1-year-mortality of VinV-TFAVI and redo surgery for failing aortic bioprostheses (re-SAVR). Methods and results: Patients receiving either VinV-TFAVI (n = 147) or re-SAVR (n = 111) for a degenerated aortic bioprosthesis between 01/2006 and 05/2017 were included in this analysis. All-cause 1-year mortality was the primary outcome measure. Early safety and clinical efficacy according to VARC-2 endpoint definitions were evaluated at 30 days. Baseline characteristics differed significantly between both groups including age, STS-PROM, and incidence of relevant comorbidities. Re-stenosis was the predominant mode of failure in 45.9% of re-SAVR and 63.1% of VinV-TFAVI patients. The rate of "early safety" endpoints was lower with VinV-TFAVI (17.7% vs. 64.9%, p < 0.01), the rate of "clinical efficacy" endpoints was lower, e.g. better with re-SAVR (53.1% vs. 32.4%, p < 0.01). All-cause 1-year-mortality (VinV-TFAVI 8.8% vs re-SAVR 9.9%, p = 0.84) was not different. Treatment strategy was not associated with 1-year-mortality in a Cox regression analysis. The incidence of prosthesis-patient-mismatch was higher in VinV-TFAVI compared to re-SAVR. Conclusion: VinV-TFAVI represents a viable alternative for treatment of degenerated aortic bioprostheses in patients at increased surgical risk. However, in patients at low risk for reoperation, a better clinical efficacy and acceptable safety may favour re-SAVR. Highlights: VinV-TAVI is a safe and effective treatment for degenerated aortic bioprosthesis. Data comparing this procedure to redo surgery (re-SAVR) are scarce. Comparable 1-year-mortality between re-SAVR and VinV-TFAVI. Incidence of bleeding and renal failure was higher with re-SAVR. Postoperative transvalvular gradients were higher after VinV-TFAVI.